HUBUNGAN KEPADATAN SIPUT (Drupella) DENGAN KONDISI EKOSISTEM TERUMBU KARANG DI PERAIRAN PULAU SEMUJUR PROVINSI KEPULAUAN BANGKA BELITUNG - ISTIQOMAH ISTI QOMAH; Okto Supratman; Indra Ambalika Syari; Okto Supratman (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2019)
This research aims to analyse density of Drupella's on coral reef ecosystem, analyze the percentage of coral cover and analyze the relationship between the density of Drupella with environmental factors and conditions coral reef ecosystem in the waters of Semujur Island. Research data retrieval in April 2019 in the waters of Semujur Island. Drupella data retrieval using Belt Transect method and coral reef data retrieval using Line Intercept Transek. The results showed that the highest overall density of Drupella is in the area of coral, which is 244 ind/100m2 and the lowest density of Drupella is in the landscaped area of 31 ind/100m2, coral cover percentage Highest in the area of coral average of 72.20% and the lowest 23.44% while on the highest cover area of 54.96% and lows of 29.14%. Principal Component Analysis (PCA) in the reef flats and Drupella watersheds correlates with temperature, current, pH, Dissolved Oxygen and Total Suspended Solid. Correspondence Analysis (CA) in the reef flats was found that Drupella was positively correlated with lifeforms acropora submassive, acropora tabulate, coral submassive, and coral massive. In the slope area of the Drupella positively correlated with the type of lifeform acropora digitate, acropora submassive, acropora tabulate, coral submassive, and coral branching.